PENGARUH SERAT AMPAS TAHU DAN TEMPE GEMBUS TERHADAP PROFIL ASAM LEMAK RANTAI PENDEK DALAM DIGESTA TIKUS Wistar = EFFECTS OF SOY PULP AND FERMENTED SOY PULP FIBER ON SHORT CHAIN FATTY ACID PROFILE IN THE DIGESTA OF Wi - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1999)
ABSTRACT Study on the nutritional properties of fiber extracted from soy pulp and fermented soy pulp has been conducted in rats. The aim of this study is to investigate the effects of those fibers on weight, water content, pH and SCFA profile of the digesta. Five groups of six male Wistar rats were used. They were fed a standard diet based on modified AIN-93 formula i.e TL diet (high lipid), TS diet (cellulose), AT diet (soy pulp) TG diet (fermented soy pulp), and control diet, All of the diets contain 3,3% of cholesterol except for the control diet and given to the rats ad libitum for 30 days. At the end of the research, the rats were excecuted and digesta were taken and analyzed for water content, weight, pH and SCFA profile. It was found that cellulose, soy pulp and fermented soy pulp increase moisture content and weight but decrease the pH of the digests, similarly. The fiber diets (TS, AT adn TG diet) resulted in similar profile of SCFA with acetic (>60%), propionic (>20%) and butyric acid (